Adjustments to the Classification of Forms of Modern Multinational Spanish Language as a Linguistic System - Svetlana Nikíforova (Ибероамериканские тетради, 2018)
The main objective of the research: The article analyzes a notion of a “national variant of multinational language” introduced by the academic G.V. Stepánov, as well as a classification of forms of modern multinational Spanish language as a linguistic system elaborated by the academic N. M. Fírsova.The research methods and the methodology used: To conduct this research the author has been analyzing theoretical literature on the subject; examining constitutions and legislative acts related to political status of Spanish-speaking countries and regions; using materials collected while writing the doctoral thesis and author’s own experience obtained during her multiple trips to Spain and Latin American countries. Also, the following research methods have been used: descriptive, comparative, functional, structural and statistical methods, a tracking method for development of linguistic phenomena and a linguocultural analysis method.The main findings of the research: 1. The existence in the modern world of multiple state structure forms, as well as often indeterminate legal status of a language within those forms, sometimes prevent us from determining which political formation should be viewed as an independent state and which language would be considered as an official / state one in each specific case. We believe some adjustments should be introduced to the classification of the existing Spanish language forms elaborated by the academic N. M. Fírsova. It is necessary to remove the “state language” characteristic from the P.I called “National Variant of Spanish Language” which will lead to replacing the term “national variant” with “regional variant”. 2. The ideas of political, religious, legal and other equality of any minority groups and communities that spread in the last decades and a so-called “transfer of Europe of the states to Europe of the regions” are gradually shattering the hierarchy of language forms in linguistics. Thus, the hierarchical status of the “dialect” rises to the level of the “national variant”. On the one hand, we propose to introduce the “prestige” characteristic of the language into the classification, and, on the other hand, to unify the notions of the “regional variant” and the “dialect” into a single category of the “regional variant”. 3. We propose to create a paragraph called “Subdialect” and consider it as the smallest territorial variety of a language. 4. We propose to consider a possibility of merging together the paragraphs II (“territorial variant”) and III (“territorial dialect”) of N.M.Fírsova’s classification.The main conclusions: A new classification of language forms where the language represents a linguistic system with a new set of characteristics corresponding to each point is introduced for discussion. As a result, it is proposed to replace the term “multinational language” with the term “multi-variant language”.